From paradox to policy: the problem of energy resource conservation in Britain and America, 1865-1981 - Turnbull, T (2017)
The idea that we can 'save energy' has become a commonplace homily. But with a moment's reflection it is clear there is nothing self-evident about saving energy. Do we save fuel or a system’s ability to 'do work'? Do we conserve for perpetuity or to prolong use? Is the motivation resource economy, scarcity, productivity, or - more recently - climate change mitigation? And what stops the fruits of individual parsimony being consumed elsewhere? This thesis offers a history of the idea that we can conserve energy by using it more efficiently. In recounting this story, it is argued that conserved energy is a 'metrological resource' produced by practices of measurement, calculation, and computation. A second argument is that the history of ERC offers an under examined example of a 'resource ontology’; the social processes through which nature is imbued with utility and value. Accordingly, the study of, what is termed, energy resource conservation (ERC herein) involved a novel research method which focused upon the scientific and intellectual processes of resource making, as much as the material. This thesis begins in 1865 with the publication of William Jevons' The Coal Question (1865), in which the resource conservative principles of Classical political economy were overturned. Jevons argued that increased efficiency of coal use would serve only to increase the rate and scale with which coal was used. Proceeding from this anti-thesis, the following chapters outline how, irrespective of Jevons' claim, policies based on the principles of scientific management were applied to the conservation of fuel resources for conserving natural resources. In pre-war America, a complex system of 'pro-rationing' extraction licenses were introduced to conserve the productive capacity of petroleum wells. However, a significant shift occurred during the Cold War, as the conservation of fuel became increasingly conflated with the econometrician's notion of efficient resource allocation. But the most significant developments occurred in the nineteen-seventies, in response to a perceived crisis in energy supply. Fuel policy became a more systemic 'energy policy', which drew on scientific management, graph theory, systems theory, statistical mechanics, and computational econometrics in an attempt to quantify and demonstrate how society could act to conserve energy resources by increasing the efficiency of energy use. The resulting science, and its concomitant policies were an odd mix of cold war rational decision making theories, détente science, scientific radicalism, and liberal economic theory, all given a countercultural and environmentalist gloss in the latter half of the decade. On the basis of this conflation of ideas, a new approach to energy saving that emerged, which transformed the principles of energy resource governance, shifting the onus to conserve from producer to consumer, with distinct implications for post-war theories of political economy.